1998
DOI: 10.1159/000016444
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Dentin Demineralization by Fluoride in vitro

Abstract: Compared with the knowledge accumulated on enamel-fluoride interactions, relatively little data is available regarding fluoride effects on dentin. This applies to both laboratory and clinical studies into the efficacy of fluoride schemes for the prevention of root surface caries. This study aimed to determine the effects of fluoride and pH on the demineralization of dentin, such as to provide information necessary to develop preventive programmes. Bovine dentin blocks were subjected to undersaturated calcium- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(42 citation statements)
references
References 14 publications
2
34
0
6
Order By: Relevance
“…According to ten Cate et al 26,27) , demineralization inhibition depends on fluoride concentration, and microradiographic data in vitro showed that 2 ppm fluoride in artificial saliva containing calcium and phosphate at pH 4.5 inhibited demineralization of enamel lesions, while dentin demineralization was inhibited in clinically relevant percentages (40%) at fluoride levels above 1 ppm. However, these fluoride concentrations would be toxic in clinical situations 28) . In our study, the total amounts of fluoride released were 5.61, 9.86, 18.1 and 30.4 ppm/3 ml/ day of the 5, 10, 20 and 30 wt% specimens respectively on day 16.…”
Section: Discussionmentioning
confidence: 99%
“…According to ten Cate et al 26,27) , demineralization inhibition depends on fluoride concentration, and microradiographic data in vitro showed that 2 ppm fluoride in artificial saliva containing calcium and phosphate at pH 4.5 inhibited demineralization of enamel lesions, while dentin demineralization was inhibited in clinically relevant percentages (40%) at fluoride levels above 1 ppm. However, these fluoride concentrations would be toxic in clinical situations 28) . In our study, the total amounts of fluoride released were 5.61, 9.86, 18.1 and 30.4 ppm/3 ml/ day of the 5, 10, 20 and 30 wt% specimens respectively on day 16.…”
Section: Discussionmentioning
confidence: 99%
“…LD, however, may be controlled by the pH of the solution rather than by the fluoride ion concentration 25) , suggesting that LD may not be an accurate parameter for measuring demineralization.…”
Section: Discussionmentioning
confidence: 99%
“…This was consistent with previous studies showing the existence of linear relationships between the square root of the duration of demineralization and various parameters for quantifying the degree of demineralization (elution of calcium ions or phosphate ions) when specimens are demineralized under consistent demineralization conditions 21) . It is widely known that fluoride inhibits dentin demineralization and arrests caries progression 18,22,23) . In the present investigation, significant differences in CT depth between both fluoride and control groups were evident after the first day of demineralization ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Five microliters of the fluoride solution concerned was dropped onto the specimen surfaces in the NaF and APF groups and left for 5 min, after which the specimens were rinsed with distilled water and the remaining water was wiped off. The specimens were then immersed in demineralizing solution (2.2 mM CaCl 2, 2.2 mM KH2PO4, 50 mM CH3COOH, 3.1 mM NaN3, pH 5.02) 18,19) , and 10 specimens in each group were left in the demineralization solution at a constant temperature of 37ºC for 1, 3, 7, 14 and 21 days each. The demineralization solution was replaced with fresh solution at 7-day intervals 20) .…”
Section: Preparation Of Root Dentin Specimensmentioning
confidence: 99%